Urgensi Penegakan Hukum terhadap Kasus Pencurian Sepeda Motor oleh Anak Muda di Kota Medan: Studi Putusan Nomor: 1816/Pid.B/2023/PN MDN - Nur Janna; Putri Adinda Manurung; Rohma Safitri; Isnaniah Isnaniah; Parlaungan Gabriel Siahaan; Dewi Pika Lbn Batu (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Theft cases are the most common cases that are most disturbing to the public and detrimental to the parties involved. The law on theft no longer makes perpetrators of theft feel afraid of sanctions. Even though it is very clear that theft is classified as a criminal offense that will be punished according to the level of the theft case. The type of research carried out is empirical legal research, empirical legal research is a type of research that aims to look at the law as a whole and examine how the law functions in society. Empirical legal research methods can also be referred to as sociological legal research because the focus of this research is examining people in their social relationships. And the data collection techniques used were interview methods and literature studies. In the research, the data used is primary data in the form of statements from the Medan Police and the Medan District Court regarding motorbike theft. The results of the discussion were that each defendant was sentenced to prison for 4 (four) years. Causative factors include family or parental factors, environmental factors, economic need factors, and low education factors.